Antioxidant processes involving epicatechin decreased symptoms of pine wilt disease - Zhang, Ruizhi; Wang, Jianan; Xia, Rui; Li, Danlei; Wang, Feng (Frontiers in Plant Science, 2022)
Since the pine wood nematode (PWN, Bursaphelenchus xylophilus) invasion of Northeast China, both symptomatic and asymptomatic PWN carriers have been found. Asymptomatic PWN carriers, which are more dangerous than symptomatic carriers, constitute a source of infection in the following spring. The simultaneous presence of symptomatic and asymptomatic PWN carriers indicates that Pinus koraiensis has different tolerance levels to PWN. In this study, validity of susceptibility testing discovers differential types of P. koraiensis including Latent Reservoirs, Low Susceptibles, High Susceptibles and Bell Ringers. Among those types, the Low Susceptibles and Latent Reservoirs were asymptomatic PWN carriers, and Latent Reservoirs were the most dangerous. Transcriptome and metabolomic data showed that 5 genes (3 ans and 2 anr gene) involved in the epicatechin (EC) synthesis pathway were significantly upregulated, which increased the content of EC antioxidants in Latent Reservoirs. Then, the hypersensitive response (HR) and hydrogen peroxide (H2O2), which functions as a signaling molecule in systemic acquired resistance, decreased. However, low contents of EC and high contents of H2O2 were found in the High Susceptibles of P. koraiensis. These results show that the susceptibility of P. koraiensis to PWN differed among different individuals, although no resistant individuals were found. Latent Reservoirs, in which more PWNs resided without visible symptoms via prolonged incubation period, inhibited the symptoms caused by H2O2 because of increased contents of the EC antioxidants.